Pentoxifylline in the Treatment of Cutaneous Leishmaniasis: A Randomized Clinical Trial in Colombia - Maria del Mar Castro; Alexandra Cossio; Adriana Navas; Olga Fernandez; Liliana Valderrama; Lyda Cuervo-Pardo; Ricardo Marquez-Oñate; María Adelaida Gómez; Nancy Gore Saravia (Pathogens, 2022)
Addition of the immunomodulator pentoxifylline (PTX) to antimonial treatment of mucosal leishmaniasis has shown increased efficacy. This randomized, double-blind, placebo-controlled trial evaluated whether addition of pentoxifylline to meglumine antimoniate (MA) treatment improves therapeutic response in cutaneous leishmaniasis (CL) patients. Seventy-three patients aged 18–65 years, having multiple lesions or a single lesion ≥ 3 cm were randomized to receive: intramuscular MA (20 mg/kg/day × 20 days) plus oral PTX 400 mg thrice daily (intervention arm, n = 36) or MA plus placebo (control arm, n = 37), between 2012 and 2015. Inflammatory gene expression was evaluated by RT-qPCR in peripheral blood mononuclear cells from trial patients, before and after treatment. Intention-to-treat failure rate was 35% for intervention vs. 25% for control (OR: 0.61, 95% CI: 0.21–1.71). Per-protocol failure rate was 32% for PTX, and 24% for placebo (OR: 0.50, 95% CI: 0.13–1.97). No differences in frequency or severity of adverse events were found (PTX = 142 vs. placebo = 140). Expression of inflammatory mediators was unaltered by addition of PTX to MA. However, therapeutic failure was associated with significant overexpression of il1β and ptgs2 (p < 0.05), irrespective of study group. No clinical benefit of addition of PTX to standard treatment was detected in early mild to moderate CL caused by Leishmania (V.) panamensis.